Teachers’ beliefs about assessment in an efl context in colombia (2012)
There is evidence that teachers’ beliefs on teaching and learning exert an influence on the way they teach and assess learning, and on what students learn. Therefore, it is central that overt attention is devoted to the perceptions teachers have and how they influence teaching and learning. In this article we describe a study on teachers’ beliefs about assessment, in general, and about the assessment systems used at a language center of a private university in Colombia. Surveys, written reports, and interviews were used to research the beliefs of sixty-two teachers. Results indicate a contradiction between what they say they do and what they believe, suggesting that teachers need opportunities for reflection, selfassessment and more guidance on formative assessment practices. Diferentes estudios evidencian que las creencias de los profesores acerca de la enseñanza y el aprendizaje influyen tanto en la manera de enseñar y evaluar como en lo que los estudiantes aprenden. Consecuentemente, es necesario prestar atención a las percepciones de los profesores y a cómo estas influyen en la enseñanza y el aprendizaje. En este artículo describimos un estudio realizado en un centro de idiomas de una universidad privada en Colombia, sobre las creencias de los profesores respecto a la evaluación en general y a los sistemas de evaluación que se usan allí. Exploramos las creencias de sesenta y dos profesores mediante encuestas, reportes escritos y entrevistas. Los resultados indican una contradicción entre lo que los profesores dicen hacer y lo que creen. También sugieren que los profesores necesitan oportunidades para la reflexión, la autoevaluación y más orientación en prácticas de evaluación formativa.